La ocupación del espacio en el sur de Pozuelos (Jujuy, Argentina) durante tiempos prehispánicos y coloniales - Angiorama, Carlos I. (Estudios Sociales del NOA)
Despite hosting one of the most emblematic archaeological sites of the Puna, the Pukara of Rinconada, Southern Pozuelos remained virtually unknown from an archaeological point of view. Our research, which started in 2005, is focused on the different ways of the inhabitants space occupation and its transformation through times, from the archaic to the colonial period. In this paper we present a brief summary of our research results.